Making the connection: thoughts on the conceptual evolution of two short films - Carstens, Luke (My University, 2009)
Abstract This dissertation examines the conceptual developments of two of the writer’s short films. The research consists of several components: films produced between 2004 – 2005, including commentaries that provide description and analyse of the techniques and processes used in the production of the works; and a written component that explores some the conceptual backgrounds and interpretations of the films presented.